Morphological ontogeny of Conoppia palmicincta (Acari, Oribatida, Cepheusidae) - Seniczak, Stanisław; Seniczak, Anna (Zootaxa, 2024)
The morphological ontogeny of Conoppia palmicincta (Michael, 1880) is described and illustrated. The adult of this species is poorly known, but the tritonymph is relatively well known as one of the most beautiful oribatid mites. The juveniles of this species are light brown, roundish and flattened. Most prodorsal setae of the juveniles are setiform (short ro, le and ex; long bs), except for phylliform and reticulate in. The larva has 11 pairs of gastronotal setae, including h2, the nymphs have 12 pairs (h3 and p-series are added, and d-series is lost). Most gastronotal setae of juveniles are wide, phylliform, reticulate and occupy the marginal parts of gastronotum, except for five setiform setae in the larva (very long c3 and h1, medium sized h2 and short da and dm), and four setiform setae in the nymphs (very long c3 and h2, long p2 and shorter p3). The nymphs are eupheredermous, i.e. they lose their dorsal seta of d-series and carry the exuvial scalps of previous instars on the gastronotum. Most leg setae of juveniles are setiform, except for three wide, phylliform setae on leg I of larva (l on genu and l’ on tibia), from which l’’ on genu is reticulate, while l’ on genu and tibia has longitudinal lines. Relatively long are seta l’’ on tibia I of larva, and l’’ on tibia I and II of the nymphs. Seta d accompanies solenidion σ on genua I–III and φ on tibiae II–IV.